2023
DOI: 10.3389/fimmu.2023.1139620
|View full text |Cite
|
Sign up to set email alerts
|

Non-spike and spike-specific memory T cell responses after the third dose of inactivated COVID-19 vaccine

Abstract: BackgroundDuring the COVID-19 epidemic, vaccination has become the most safe and effective way to prevent severe illness and death. Inactivated vaccines are the most widely used type of COVID-19 vaccines in the world. In contrast to spike-based mRNA/protein COVID-19 vaccines, inactivated vaccines generate antibodies and T cell responses against both spike and non-spike antigens. However, the knowledge of inactivated vaccines in inducing non-spike-specific T cell response is very limited.MethodsIn this study, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…By triggering a strong cellular immune response, it synergizes with the B cell response, leading to the long-term success of the vaccine [ 24 ]. Furthermore, it has been reported that the frequencies of cytokine-secreting non-spike specific CD4+ and CD8+ T cells correlate well with those of the spike-specific T cellsfrom WT, Delta, and Omicron strains [ 25 ]. Despite partial broad-spectrum protection observed in animal studies, there are currently no broad-spectrum vaccines available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…By triggering a strong cellular immune response, it synergizes with the B cell response, leading to the long-term success of the vaccine [ 24 ]. Furthermore, it has been reported that the frequencies of cytokine-secreting non-spike specific CD4+ and CD8+ T cells correlate well with those of the spike-specific T cellsfrom WT, Delta, and Omicron strains [ 25 ]. Despite partial broad-spectrum protection observed in animal studies, there are currently no broad-spectrum vaccines available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…As antigenic changes in these conserved internal structural proteins are seldom observed in VOCs, T-cell immunity against these proteins is unlikely to be impacted by antibody escape mutations in VOCs. Therefore, inactivated COVID-19 vaccines are likely to remain effective against existing and future variants of SARS-CoV-2 [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…to enhance the neutralizing antibody titers against various virus variants, such as Beta, Gamma, Delta, and Omicron (Arashiro et al, 2023;Boaventura et al, 2023). Moreover, the T-cell response is also improved after a third dose (R. Huang et al, 2023). Taken together, the finding that booster vaccinations induce a higher titer of…”
Section: Vaccine Effectiveness Against Sars-cov-2 Variantsmentioning
confidence: 94%